Upgrading and repairing PCs - Mueller, Scott; Safari eBooks ([Place of publication not identified] : Que, 2015)
"Learn from the undisputed PC hardware champion, Scott Mueller! This two-hour, studio-quality how-to video is playable on your DVD player or computer! In this video, Scott Mueller delivers a complete seminar on PC troubleshooting, teaching you how to identify and resolve an array of common and not-so-common PC problems. Scott provides detailed explanations for all the tools that should be standard issue part of any PC toolkit, as well as explaining critical rules you should follow to safely operate on your PC's internal components. In these videos, Scott ensures that you are equipped to handle any PC hardware problem. From there, Scott takes you through a complete disassembly of an All-in-One (AiO) system, showing just what you can do to keep these specialized systems running smoothly. Finally, Scott gives you a detailed look at today's ultra-fast, solid-state disk drives (SSD) and the benefits they bring to modern systems."--Resource description page.
Title taken from resource description page (Safari, viewed August 31, 2015).
Presenter, Scott Mueller.
Keywords: Microcomputers -- Upgrading; Microcomputers -- Repairing; Electronic books